Kedudukan hukum atas Tanah Grondkaart sebagai bukti penguasaan tanah dalam Hukum Positif di Indonesia - Agra Hayyudya Arika, Cindy; Masykur, Hamidi; Supriyadi , Bambang Eko (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Land ownership must be followed by evidence, so in this case the urgency of proving ownership of land rights is essential, so that it must produce products that have legal certainty of ownership of land. However, proving land ownership has always invited polemics, especially the legacy of railroad assets during the Dutch colonial era in the form of a map, namely "Grondkaart" which is currently the proof of rights owned by PT KAI (Persero). "Grondkaart" is still an issue because of its evidentiary power and its position has an impact on proving land rights that are in accordance with Law Number 5 of 1960 (UUPA), Government Regulation Number 24 of 1997, and Government Regulation Number 18 of 2021, so it becomes an urgency to examine issues related to its legal position as proof of land tenure by PT KAI (Persero) in Positive Law in Indonesia. This research uses a normative juridical research approach, namely tracing the laws and regulations related to the issues raised in this study.